A Re-Consideration of the Excavations on Tell Ingharra (East Kish), 1923-33 - Moorey, P. R. S.
Appendix I (45-50): Objects, now in the Ashmolean Museum, Oxford, from grave groups in the ‘Y’ sounding. Appendix II (50-51): Notes on the sherds in the Ashmolean reported from outside the graves in ‘Y’ sounding.